Breast-feeding and adherence to infant feeding guidelines do not influence bone mass at age 4 years. - Harvey, N; Robinson, S; Crozier, SR; Marriott, L; Gale, C; Cole, Z; Inskip, H; Godfrey, K; Cooper, C (2009)
The impact of variations in current infant feeding practice on bone mineral accrual is not known. We examined the associations between duration of breast-feeding and compliance with infant dietary guidelines and later bone size and density at age 4 years. At total of 599 (318 boys) mother-child pairs were recruited from the Southampton Women's Survey. Duration of breast-feeding was recorded and infant diet was assessed at 6 and 12 months using FFQ. At 6 and 12 months the most important dietary pattern, defined by principal component analysis, was characterised by high consumption of vegetables, fruits and home-prepared foods. As this was consistent with infant feeding recommendations, it was denoted the 'infant guidelines' pattern. At age 4 years, children underwent assessment of whole-body bone size and density using a Hologic Discovery dual-energy X-ray absorptiometry instrument. Correlation methods were used to explore the relationships between infant dietary variables and bone mineral. There was no association between duration of breast-feeding in the first year of life and 4-year bone size or density. 'Infant guidelines' pattern scores at 6 and 12 months were also unrelated to bone mass at age 4 years. We observed wide variations in current infant feeding practice, but these variations were not associated with differences in childhood bone mass at age 4 years.